Using Integrative Analysis of DNA Methylation and Gene Expression Data in Multiple Tissue Types to Prioritize Candidate Genes for Drug Development in Obesity - Guo, Qingjie; Zheng, Ruonan; Huang, Jiarui; He, Meng; Wang, Yuhan; Guo, Zonghao; Sun, Liankun; Chen, Peng (Frontiers in Genetics, 2018)
Obesity has become a major public health problem which is caused by a combination of genetic and environmental factors. Genome-wide DNA methylation studies had identified that DNA methylation at Cytosine-phosphate-Guanine (CpG) sites associated with obesity. However, subsequent functional investigations were hampered by numerous associated loci. In this study, we applied an integrative analysis approach aiming to prioritize the drug development candidate genes from many associated CpGs. Association data was collected from previous genome-wide DNA methylation studies and combined together using a sample-size-weighted strategy. Gene expression data in adipose tissues and enriched pathways of the affiliated genes were overlapped to shortlist the associated CpGs. The CpGs with the most overlapping evidences were located as the most appropriate CpGs for future studies. Our results revealed that 119 CpGs were associated with the obesity (p<1.03×10-7). Of the affiliated genes, SOCS3 was the only one involved in all enriched pathways and differentially expressed in both visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT). In conclusion, our integrative analysis is an effective approach in highlighting the DNA methylation of most drug development relevance. SOCS3 may serve as a target for drug development of obesity and its complications.